Principles and Practice of Marketing. - Jobber, David, 1947-; Ellis-Chadwick, Fiona (2016)
This textbook on marketing includes information on branding, ethics and corporate social responsibility, relationship marketing, internet marketing, mobile, wireless and e-mail marketing and adverts to demonstrate marketing principles in practice.
Previous edition: 2013.
Includes QR codes.
Includes bibliographical references and index.
Keywords: Marketing; Marketing -- Europe -- Case studies; Business and Management